Skinny bitch book of vegan swaps - Barnouin, Kim (HarperOne, 2012)
With more options comes more confusion (such as the emerging issue of vegan junk food), and THE SKINNY BITCH BOOK OF VEGAN SWAPS presents clear swaps for foods that you may think are healthy, clearly explaining what makes one choice better than another, exposing imposters, and explaining how to easily spot the difference. Barnouin's fun, no-nonsense voice and vast expertise sparkle on every page, and in helpful lists like "Worst Veggie Dishes That You Think are Healthy," "Top Ten Worst Pesticide Ridden Veggies & Fruit," and the never-travel-without-it "Top Ten Things to Eat While Stranded in an Airport." Best of all, she knows that the concerns of today's savvy eaters' run the gamut from calories to carbon footprints, and takes it all into account.